Men, Animals and Pots. A few Thoughts about a Narrative Motive on Syrian Bronze Age Vessels - Mas, Juliette (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2017)
Mesopotamian Bronze Age decorated pottery is unusual. Beyond very specific decorated styles, such as Scarlet Ware, Ninevite 5, Smeared Washed Ware and Khabur Ware, examples of decorated pots are very few. Furthermore, decorated pots usually present a very standardized decorative repertoire of geometrical patterns. Nevertheless, there are a few examples of complex and figurative motives. Attention will be focused here on four Bronze Age pots coming from three different Upper Mesopotamian sites. These pots present narrative scenes combining vegetal, animal, and human figures.